What is Africanness? Contesting nativism in race, culture and sexualities - Charles Ngwena (Pretoria University Law Press (PULP), 2018)
What is Africanness: Contesting nativism in culture, race and sexualities, by Charles Ngwena, Professor of Law at the Centre for Human Rights, Faculty of Law, University of Pretoria, is a peer-reviewed monograph aiming to contribute to the ongoing scholarly conversation in and beyond South Africa about who is African and what is African. It aims to implicate a reductive sameness in the naming of Africans ('nativism') by showing its teleology and effects; and offers an alternative understanding of how Africans can be named or can name themselves. The book develops an epistemology for constructing the hermeneutics of Africanness today, long after the primal colonial moment and its debasing racialising ideology. It interrogates the making of Africa in colonial discourses and the making of an African race and African culture(s) and sexuality(ies) in ways that are not just historically conscious but also have a heuristic capacity to contest nativism from the outside as well as from within. The arguments in this book go beyond problematising African identity by addressing an existential gap in theory for explicating African social identity. The book develops an interpretive method - a hermeneutics - for locating and deciphering African identifications in ways that are historically conscious and conjunctural. The hermeneutics look to the present and the future in addition to the past, so that African identifications are not nailed to a mast but remain invested with mobility and the capacity to mutate radically and make new and unexpected beginnings.